ANALISIS TINGKAT KECACATAN PADA CHILDPART BUTTON REALESE DENGAN MENGGUNAKAN METODE VISUAL CHECK DAN (4 QC) TOOLS DI PT. XYZ - Tarnoto Tarnoto; Wahyudin Wahyudin; Dene Herwanto (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2021)
This research focuses on analysis of childpart button realese parking brake component in PT. XYZ. The purpose of this research is to improve the quality produced by the company and minimize the occurrence of disability in the childpart button realese into the assembly process. The method used is a descriptive method that’s is a research method by collecting data that describes systematically and accurately. Data collection techniques in this study use observation directly to PT. XYZ, with the help of statistic tool with visual check method and 4 QC tools in PT. XYZ. visual check method can help a QC Inspector to know the defects in childpart button realese component, after that assisted by 4 QC tools method consisting of histogram diagram, pareto diagram, P control map (P-Chart) and casual diagram. Observations during practical work at PT. XYZ, that the data type of incompatibility on the component childpart button realese with the total number of samples taken at the time of practice work as much as 3.950 pcs with 15 days of sampling data. Of the 3.950 pcs there are different types of damage, including scratch, spots, bubbles, and grafients and the highest of the four types of damage is the type of scratch damage with a percentage of 33,96%. therefore the anticipation so that the occurrence of defective products (not good) into the assembly procces, QC inspector provides a strict examination in the process and when the product is finished (finish good) lever assy parking brake.